Gadd45 Stress Sensor Genes - Liebermann, Dan A.; Hoffman, Barbara; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Emerging evidence indicates that the Gadd45 family of genes play a unique and critical role as sensors of stress, including genotoxic, physiological and oncogenic stress.   The stress response Gadd45 family of genes (Gadd45a, Gadd45b & Gadd45g), discovered by Dr. Liebermann and other researchers, encode for small (18 kd) nuclear/cytoplasmic proteins).  These genes are rapidly induced by a wide variety of endogenous and exogenous stress stimuli. In spite of marked similarities, Gadd45 genes are regulated differently & exhibit functional diversity.  Gadd45 are implicated in cell cycle arrest, DNA demethylation & repair, apoptosis, cell survival, genomic stability, inflammation, & in response to physiological and oncogenic stress.   Functions of Gadd45 genes are mediated by protein-protein interactions that modulate structure/function of other cellular proteins implicated in cell cycle regulation and the response of cells to stress; these interactions vary depending upon the biological setting including cell type, developmental stage and stress/stimulus.  Protein partners include cdc2/cyclinB1, p21, the p38/JNK stress induced kinase pathways, and PCNA/histones. The purpose of this book is to provide a comprehensive picture of the unique global role Gadd45 genes play as stress sensors & the molecular pathways involved.  .
Gadd45 in stress signaling, cell cycle control and apoptosis -- Gadd45 in Modulation of Solid Tumors and Leukemia -- Gadd45 Proteins: Key players of repair-mediated DNA demethylation -- Gadd45 proteins in Immunity -- Gadd45 in the liver — Signal transduction and transcriptional mechanisms -- The Role of the Gadd45 Family in the Nervous System: A focus on Neurodevelopment, Neuronal Injury, and Cognitive Neuroepigenetics -- Gadd45 stress sensors in preeclampsia -- Index.
Keywords: Medical genetics; Biochemistry; Human genetics; Gene Function; Biochemistry, general; Human Genetics